The long multi-epitope peptide vaccine combined with adjuvants improved the therapeutic effects in a glioblastoma mouse model - Tran, Thi-Anh-Thuy; Kim, Young-Hee; Kim, Ga-Eun; Jung, Shin; Kim, In-Young; Moon, Kyung-Sub; Kim, Young-Jin; Lee, Tae-Kyu; Yun, Hyosuk; Lee, Je-Jung; Lee, Hyun-Ju; Lee, Chul Won; et al. (Frontiers in Immunology, 2022)
Emerging data have suggested that single short peptides have limited success as a cancer vaccine; however, extending the short peptides into longer multi-epitope peptides overcame the immune tolerance and induced an immune response. Moreover, the combination of adjuvants such as lenalidomide and anti-programmed cell death protein 1 (PD1) with a peptide vaccine showed potential vaccine effects in previous studies. Therefore, the effects of a long multi-epitope peptide vaccine in combination with lenalidomide and anti-PD1 were analyzed in this study. Long multi-epitope peptides from two MHCI peptides (BIRC597-104 and EphA2682-689) and the pan-human leukocyte antigen-DR isotype (HLA-DR) binding epitope (PADRE) were synthesized. The therapeutic effects of long multi-epitope peptides in combination with lenalidomide and anti-PD1 were confirmed in the murine GL261 intracranial glioma model. Immune cells’ distribution and responses to the long multi-epitope peptides in combination with these adjuvants were also estimated in the spleens, lymph nodes, and tumor tissues. The difference between long multi-epitope peptides and a cocktail of multi-epitope peptides combined with lenalidomide and anti-PD1 was also clarified. As a result, long multi-epitope peptides combined with lenalidomide and anti-PD1 prolonged the survival of mice according to the suppression of tumor growth in an intracranial mouse model. While long multi-epitope peptides combined with these adjuvants enhanced the percentages of activated and memory effector CD8+ T cells, the increase in percentages of regulatory T cells (Tregs) was observed in a cocktail of multi-epitope peptides combined with lenalidomide and anti-PD1 group in the tumors. Long multi-epitope peptides combined with these adjuvants also enhanced the function of immune cells according to the enhanced pro-inflammatory cytokines and cytotoxicity against GL261 cells in ex vivo. In conclusion, long multi-epitope peptides composed of MHCI peptides, BIRC5 and EphA2, and the MHCII peptide, PADRE, in combination with lenalidomide and anti-PD1 has the potential to improve the therapeutic effects of a vaccine against GBM.